Effect of gama irradiation on mortality of Tribolium castaneum (HERBST) - Muhamad, Rita (Malaysian Society of Applied Biology, 1987)
An investigation was made to assess the susceptibility of larvae and adults of Tribolium castaneum to gamma irradiation. The larvae were more susceptible to irradiation than the adults. A dose of 50 Gy killed all the larvae but higher dose of 150 Gy was required to kill all the adults. Therefore, a dose of 150 Gy was found to be the effective dose to kill both the larvae and the adults of T. castaneum.